Isolasi dan Identifikasi Senyawa Fenil Pentanoat dari Fraksi Etil Asetat Sarang Semut (Myrmecodia pendans.) - Emma J. Pongoh; Rymond J Rumampuk; Sofia S. Krisen; Hutri C. Werfete; Arfiani Rizki Paramata (Jambura Journal of Chemistry, 2022)
Ants nest (Myrmecodia pendans.) is an epiphytic plant from Papua which is used as herbal medicine. The reseacrh to isolate and identification the ethyl acetate fraction of phenyl penatnoate compounds from ant nests(myrmecodia pendans.). The isolaton process was carried out using the maceration technique, fro the purifcation and separation of compounds the thin layer chromatographic and gravity column chromathographic were used F1 isolated were obtained weighing up to 180 mg in liquid. Identification using spectroscopy Nuclear Magnetic Resonance Proton (1H-NMR) and Nuclear Magnetic Resonance Carbon (13-NMR). The result of identification of isolated F1 indicated the posibillity of a phenyl derivative compound with the proposed name 6-hydroxy-5,5-dimethyl-phenyl-pentanoate.